How Institutions Shape Uncertainty and Risk - Moura, Stephanie Tonn Goulart; Falaster, Christian Daniel; Bianchi, Christine Elena; Mazato, Érica de Souza; Espig, Laura Taysa (Internext, 2021)
Purpose: The study proposes a conceptual framework on how institutions influence risk and uncertainty. Beyond the nuances in defining the concepts in the existing literature, the role of institutions in shaping risks and uncertainties remains understudied. This paper adopts the new institutional economics (NIE) perspective to revisit the concepts of risk and uncertainty and provide a deeper reflection about its interactions with formal and informal institutions. Method: Our conceptual model is based on four propositions that support a theoretical explanation about the relationships between institutions and uncertainties, institutions and risks, and uncertainties and risks. Findings: While formal institutions have a primary role in reducing uncertainties, informal institutions can be seen as a source of risk. These findings imply firms’ strategic decisions. In this regard, we also provide a research agenda for future empirical studies in the area. Originality/value: The study highlights the importance of institutions for companies to deal with risk and uncertainties. The institutions have a primary role in defining the “known part” of the uncertainty, allowing the companies to evaluate the different scenarios for decision-making. Theoretical/Methodological Contributions: This study differentiates risk and uncertainty interaction according to institutional theory. Additionally, we offer an academic discussion of how formal and informal institutions can shape risks and uncertainties.